Draught animal power in Africa: An overview - Anderson, F.M. (Food and Agriculture Organization of the United Nations, 1984)
Highlights key aspects of the current situation of draught animal power (DAP) in Africa within the context of the research and on-farm situation; describes constraints to the Development of DAP along with suggestions on needs and options to overcome them; and briefly outlines long-term prospects of DAP use in Africa as a source of farm energy.